2020
DOI: 10.1021/acsomega.9b04368
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Calcium Oxide and Calcium Peroxide Pretreatments of Wheat Straw for Improving Biohydrogen Production

Abstract: Wheat straw was pretreated with either CaO2 or CaO to improve biohydrogen production. Both CaO and CaO2 pretreatments improved the biodegradability of the wheat straw. CaO pretreatment raised the H2 yield by between 48.8 and 163.9% at CaO contents ranging from 2 to 4%. The highest H2 yield [144 mL/g total solid (TS)] was obtained at 121 °C and 6% CaO. In addition, the highest H2 yield from wheat straw pretreated at the same temperature and dosage of CaO2 was 71.8 mL/g TS, which was higher than that of the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…However, it has been reported that the CaO pretreatment improves the degradation of both lignin and hemicellulose, increasing the availability of the cellulose fraction (Zhang et al, 2020). Thus, delignification is important to improve the enzymatic hydrolysis to achieve higher sugar yields (Silveira et al, 2015).…”
Section: Pretreatment and Enzymatic Hydrolysismentioning
confidence: 99%
“…However, it has been reported that the CaO pretreatment improves the degradation of both lignin and hemicellulose, increasing the availability of the cellulose fraction (Zhang et al, 2020). Thus, delignification is important to improve the enzymatic hydrolysis to achieve higher sugar yields (Silveira et al, 2015).…”
Section: Pretreatment and Enzymatic Hydrolysismentioning
confidence: 99%
“…Moreover, CaO 2 pretreatment under identical conditions gave a maximum H 2 yield of (71.8 mL/g TS), higher than that of the control group (43.2 mL/g TS) treated with hot water at 12 • C [72]. Considering the pretreatment costs and the capability of H 2 production, CaO proved to be a better pretreatment agent than CaO 2 [73]. Among acids, HCl and H 2 SO 4 are the most widely employed, while NaOH is a commonly used alkali for pretreatment [74].…”
Section: Acid and Alkali Pretreatmentmentioning
confidence: 89%
“…40 Additionally, the ammonia nitrogen (NH 4 + -N), TOC and pH in the liquid samples were measured according to a previous study. 41 The total carbon (C) and nitrogen (N) of wheat straw were also determined according to the method previously described by Zhang et al 41 In addition, the topography of the straw samples was measured using a scanning electronic microscope (SEM) (JEOL JSM-5600 LV, Japan) according to the method previously reported by Zhang et al 41 The changes in the functional groups in the wheat straw samples before and aer treatment with CaO 2 were evaluated using a Fourier transform infrared (FTIR) spectrophotometer (IR Prestige-21, Japan). The lignin, cellulose, and hemi-cellulose contents of the samples before and aer treatment were measured based on a previous study.…”
Section: Analysis Methodsmentioning
confidence: 99%